Facing the unutterable in Argentinian and Brazilian documentary cinema. Urondo and Herzog’s cases - Foglia, Graciela (Caracol, 2018)
Using some reflections on testimony and documentary of memory, I propose to examine and interpret similarities and differences in the procedures of construction of documentaries Paco Urondo, la palabra justa (Argentina, 2004) by Daniel Desaloms y Vlado, 30 anos depois (Brazil, 2005) by João Batista de Andrade, which deal with the life and death of the poet, journalist and militant of Montoneros Francisco Urondo (1930-1976) and Vladimir Herzog (1937-1975), also a journalist and screenwriter, linked to the PCB, both assassinated during the dictatorships of the 1970s. Both in Brazil and in Argentina, the 1970’s were marked by revolutionary struggles in search of more just societies, extreme state violence and resistance to dictatorships. However, despite the similarity of contexts, the way of representing that struggle and confronting the unspeakable of dictatorial violence has some differences that are almost constant. In order to understand the specificities of the films, I propose as a possible interpretation that in the form of the films the marks of the different policies of truth and justice carried out in each of the countries as a product of different processes of transition would be printed: in Brazil; Not agreed or less agreed in Argentina.